Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

i am given these series which converge. $a_{n}:=b_{n}:=\dfrac{(-1)^n}{\sqrt{n+1}}$ i solved this with quotient test and came to $-1$, which is obviously wrong. because it must be $0<\theta<1$ so that the series converges. my steps:

$\dfrac{(-1)^{n+1}}{\sqrt{n+2}}\cdot \dfrac{\sqrt{n+1}}{(-1)^{n}} = - \dfrac{\sqrt{n+1}}{\sqrt{n+2}} = - \dfrac{\sqrt{n+1}}{\sqrt{n+2}}\cdot \dfrac{\sqrt{n+2}}{\sqrt{n+2}} = - \dfrac{(n+1)\cdot (n+2)}{(n+2)\cdot (n+2)} = - \dfrac{n^2+3n+2}{n^2+4n+4} = -1 $

did i do something wrong somewhere?

and i tried to know whether the cauchy produkt diverges as task says:

$\sum_{k=0}^{n}\dfrac{(-1)^{n-k}}{\sqrt{n-k+1}}\cdot \dfrac{(-1)^{k}}{\sqrt{k+1}} = \dfrac{(-1)^n}{nk+n-k^2+1} = = diverging $

i am stuck here how to show that the produkt diverges, thanks for any help!

share|cite|improve this question
You should observe that each of the $n+1$ summands is (up to sign) $\ge \frac1{\sqrt{n+1}}\frac1{\sqrt{n+1}}=\frac1{n+1}$. – Hagen von Eitzen Jan 16 '13 at 7:46
yeah, i found my mistake, i didnot take the absolute value, then it will be $1$ and not -1 – doniyor Jan 16 '13 at 7:51
up vote 1 down vote accepted

$\sum_{n=0}^\infty\dfrac{(-1)^n}{\sqrt{n+1}}$ is convergent by Leibniz's test, but it is not absolutely convergente (i.e. it is conditionally convergent.)

To show that the Cauchy product does not converge use the inequality $$ x\,y\le\frac{x^2+y^2}{2}\quad x,y\in\mathbb{R}. $$ Then $$ \sqrt{n-k+1}\,\sqrt{k+1}\le\frac{n+2}{2} $$ and $$ \sum_{k=0}^n\frac{1}{\sqrt{n-k+1}\,\sqrt{k+1}}\ge\frac{2(n+1)}{n+2}. $$ This shows that the the terms of the Cauchy product do not converge to $0$, and the series diverges.

share|cite|improve this answer

Here is another solution: Observe that

\begin{align*} \sum_{k=0}^{n}\frac{(-1)^{k}}{\sqrt{k+1}} \frac{(-1)^{n-k}}{\sqrt{n-k+1}} &= (-1)^{n} \sum_{k=0}^{n}\frac{1}{\sqrt{(k+1)(n-k+1)}} \\ &= (-1)^{n} \sum_{k=0}^{n}\frac{1}{n} \frac{1}{\sqrt{\left(\frac{k+1}{n}\right)\left(1-\frac{k-1}{n}\right)}}. \end{align*}

But since

$$ \sum_{k=0}^{n}\frac{1}{n} \frac{1}{\sqrt{\left(\frac{k+1}{n}\right)\left(1-\frac{k-1}{n}\right)}} \xrightarrow[]{n\to\infty} \int_{0}^{1} \frac{dx}{\sqrt{x(1-x)}} = \pi,$$

the general term of the Cauchy product diverges. Therefore the series itself diverges. (Here, the specific value of the integral is irrelevant. It suffices to observe that the integral is positive.)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.